(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Chapter One, Introduction and importance of the research, determining the research problem and the result hypothesis, technological and cognitive development in various areas of life, especially the development in the educational field in particular, the development of strategies and teaching methods, and the development of modern theories and active and effective learning, which emphasizes the need to integrate the learner into the educational process and consider him as a participant and part of it. giving him an opportunity to think, investigate, research, and identify concepts that activate the mental aspect and mind processes and develop thinking skills, in addition to accelerating the learning process and giving the learner sufficient time to express his concept and point of view. Like basketball, which is one of the organized activities included in the curricula of colleges and departments of physical education, which consists of a set of basic skills, and there is a great overlap with the performance of the game skills and with the performance of the game itself. And for this, teachers must pay attention to teaching skills well and linking them to performance in order to reach the development of the level of skill and technical performance of skills and to make the learners reach stages and levels of good learning and performance. This educational linkage of skills and scientific work leads learners to diversify their performance from different positions and situations in the use of ball possession, passing, scoring, defense, attack, dribbling, changing positions, etc. It is considered one of the advanced cases in education and leads to the use of various exercises to find a similar status to the playing of the game.